Computational solution of stochastic differential equations. (20th August 2013) - Sauer, Timothy
Abstract : Stochastic differential equations (SDEs) provide accessible mathematical models that combine deterministic and probabilistic components of dynamic behavior. This article is an overview of numerical solution methods for SDEs. The solutions are stochastic processes that represent diffusive dynamics, a common modeling assumption in many application areas. We include a description of fundamental numerical methods and the concepts of strong and weak convergence and order for SDE solvers. In addition, we briefly discuss the extension of SDE solvers to coupled systems driven by correlated noise. WIREs Comput Stat 2013. doi: 10.1002/wics.1272 This article is categorized under: Applications of Computational Statistics > Computational Finance Statistical Learning and Exploratory Methods of the Data Sciences > Modeling Methods Algorithms and Computational Methods > Numerical Methods